Optimization of Russian primary school graduates’ self-esteem in the personality-developing learning environment - Natalia Valentinovna Ivanova; Olga Veniaminovna Suvorova (International Journal of Evaluation and Research in Education (IJERE), 2022)
The article reveals the capacity of the designed personality-developing learning environment for optimizing the establishment of self-esteem among the fourth-grade pupils of Russian primary school graduates. Negative manifestations in the development of self-esteem of children in the fourth year of schooling along with insufficient knowledge of the environmental approach to the formation of self-esteem of fourth-grade pupils, make the material of the work relevant. The theoretical basis of the article is psychological and pedagogical research of Russian scientists in the field of the educational environment and self-esteem of schoolchildren. The author provides the content of an empirical research study. There were 213 fourth-grade schoolchildren took part. It reveals the embodied conditions and opportunities aimed at improvement of fourth-grade pupils’ self-esteem in each of the components of the experimental educational environment. The study proven that the personality-developing educational environment had a positive and statistically reliable effect on the level of self-esteem of the fourth-grade schoolchildren, as well as on the level of their aspirations. Research materials are useful for educational practice to optimize the personal growth of students aged 10-11 years.